Algebro-geometric solutions to the Manakov hierarchy. Issue 4 (2nd April 2016) - Wu, Lihua; Geng, Xianguo; He, Guoliang
Abstract : The Manakov hierarchy associated with a matrix spectral problem is proposed with the aid of Lenard recursion equations. By using the characteristic polynomial of Lax matrix for the Manakov hierarchy, we introduce a trigonal curve of arithmetic genus, from which we construct the related Baker–Akhiezer function, two algebraic functions carrying the data of the divisor and Dubrovin-type equations. Based on the theory of trigonal curves, the explicit theta function representations of the Baker–Akhiezer function, the two algebraic functions, and in particular, that of solutions for the entire Manakov hierarchy are obtained.